Avaliação da metodologia de demarcação de terrenos marginais e acrescidos: estudo de caso do trecho fluminense do Rio Paraíba do Sul - Oliveira , Jussara Stutz (2019)
This paper discourse about the methodology of demarcation of marginal lands and added by the Secretariat for Federal Heritage and proposes the consideration of the flow rate corresponding to the recurrence interval of 2 years in this methodology. It was adopted the case study of the fluminense stretch of the Paraíba do Sul river. The results indicate that methodology preconized by Secretariat for Federal Heritage is not able to consider the continuous process of anthropization of Paraíba do Sul river, caused, mainly, from the implantation and operation of hydro power plants. In addition, it was possible to verify that limnimetric rulers of the studied fluviometric stations are influenced by constants alterations in the bed and occupation of the stream bank, making difficult the estimation of the ordinary flood quota. The research concludes by the suggestion of the adoption of flow rate with a recurrence interval of 2 years, as to the State Environmental Agency (INEA), due to belief that in possession of this value and the modeling of hydrodynamic flow conditions, it will be possible to establish the water levels of demarcation of the average line of flood ordinary.